2014
DOI: 10.1186/s12989-014-0050-8
|View full text |Cite
|
Sign up to set email alerts
|

Silica nanoparticles enhance autophagic activity, disturb endothelial cell homeostasis and impair angiogenesis

Abstract: Background: Given that the effects of ultrafine fractions (<0.1 μm) on ischemic heart diseases (IHD) and other cardiovascular diseases are gaining attention, this study is aimed to explore the influence of silica nanoparticles (SiNPs)-induced autophagy on endothelial cell homeostasis and angiogenesis. Methods and results: Ultrastructural changes of autophagy were observed in both vascular endothelial cells and pericytes in the heart of ICR mice by TEM. Autophagic activity and impaired angiogenesis were further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
69
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(74 citation statements)
references
References 53 publications
(59 reference statements)
5
69
0
Order By: Relevance
“…Unlike CQ, NBP/TiO 2 nanostructures did not alter the lysosomal acidity (Figure 4b), but they did induce clear lysosome dilatation (Figure 4a). Furthermore, the intracellular cytoskeleton component F‐actin is related to the fusion between autophagosomes and lysosomes 28. Similar to BafA1, NBP/TiO 2 nanostructures disrupted the distribution of intracellular F‐actin (Figure S4, Supporting Information).…”
Section: Resultsmentioning
confidence: 87%
“…Unlike CQ, NBP/TiO 2 nanostructures did not alter the lysosomal acidity (Figure 4b), but they did induce clear lysosome dilatation (Figure 4a). Furthermore, the intracellular cytoskeleton component F‐actin is related to the fusion between autophagosomes and lysosomes 28. Similar to BafA1, NBP/TiO 2 nanostructures disrupted the distribution of intracellular F‐actin (Figure S4, Supporting Information).…”
Section: Resultsmentioning
confidence: 87%
“…To the best of our knowledge, few data are available in the literature about the underlying toxic-effect mechanisms of MSNPs on peripheral and brain vasculature 6,[9][10][11][12] or on neurons. 13 No data are available on the potential effect of MSNPs on neuronal activity.…”
mentioning
confidence: 99%
“…Their findings demonstrated that Nano SiO 2 can induce autophagic activity, accompanied by NO/NOS system disorder and an inflammatory response, eventually leading to endothelial cell dysfunction via the inhibition of the PI3K/Akt/mTOR signaling pathway. Their findings also confirm that Nano SiO 2 induced endothelial cell dysfunction is associated with autophagy, which may be an important mechanism and adverse outcome pathway of cardiovascular diseases caused by nanoparticles [33]. JunchaoDuan and his team found that the cardiovascular toxicity triggered by SiNPs occurs mainly in vascular endothelium rather than cardiomyocytes.…”
Section: Nano Siomentioning
confidence: 71%
“…Duan and his team found that SiNPs induce autophagic activity in endothelial cells and pericytes, subsequently disturb the endothelial cell homeostasis and impair angiogenesis. The VEGFR2 mediated autophagy pathway may play a critical role in maintaining endothelium and vascular homeostasis [33]. The typically morphological characteristics (autophagosomes and autolysosomes) of the autophagy process were observed in TEM ultra structural analysis by Yu's team [34].…”
mentioning
confidence: 99%